Bioethics, Conflicts of Interest, the Limits of Transparency - Jansen, Lynn A. (The Hastings Center report, 2003)
The movement in bioethics toward disclosure of financial conflicts of interest is well and good, most of the time. But in some cases, disclosure is not only unnecessary but destructive. When bioethicists advance arguments whose premises and logical moves are open to scrutiny, disclosure—far from clearing the air of bias—introduces bias.